Muddled Origins in Picaresque Literature: The Foreshadowing of Chaotic Lives - Terri Schroth; Bryant Smith (Interlitteraria, 2014)
Picaresque literature is known for several specific traits: 1) firstperson narration and the protagonist’s struggle for survival and a better life; 2) the chaotic childhood, outsiderdom, and low social class of the main character; 3) frequent role changes or disguises; and 4) an inconclusive ending. This article traces the muddled genealogy and subsequent chaotic lives of four pícaros: Lazarillo de Tormes, Quevedo’s Pablos de Segovia, Bellow’s Augie March, and Defoe’s Moll Flanders.